POSSIBILITIES TO PREVENT DENTAL CARIES, PERIODONTITIS AND PERIIMPLANTITIS - Raluca Alina Dragomir; Doriana Agop Forna; Carina Balcoș; Lorelay Nassar; Mohamad Madarati; Gholamreza Shokraei; Dana Nicoleta Mihai; Liana Popa; Davidescu Alexandra; Carmen Stelea (Romanian Journal of Medical and Dental Education, 2021)
The prevention of oral diseases (dental caries, periodontal disease, peri-implant diseases) must become the main way to act both individually and in community in order to reduce the risk of local and loco-regional complications and to reduce the financial burden of secondary and tertiary prevention of these diseases.